Pengaruh Disiplin Kerja Dan Keselamatan Dan Kesehatan Kerja (K3) Terhadap Kinerja Karyawan PT. KMK Global Sport K1 - Tri Wiyono; Nurhilah Lestari; Safriadi M Yunus Aks (INVESTASI : Inovasi Jurnal Ekonomi dan Akuntansi, 2025)
KMK Global Sport K1 Tangerang, particularly in the production department, work-related accidents have fluctuated over the past year. One of the contributing factors to these accidents is the lack of employee awareness regarding the importance of work discipline, which has led to a loss of workdays due to these accidents. This, in turn, has resulted in decreased employee performance. This study aims to examine the impact of work discipline and occupational health and safety (K3) on employee performance at PT. KMK Global Sport K1 Tangerang. This research is a quantitative study. The population of this research consists of 93 production employees at PT. KMK Global Sport K1 Tangerang. The sample was determined using the Slovin method, resulting in 76 employees. The data used in this study is primary data, collected through questionnaires distributed to the respondents. The primary data was processed using the Statistical Package for Social Science (SPSS) with simple regression analysis and path analysis methods. Simple regression analysis is used to test the direct relationship between variables, while path analysis is used to test the indirect relationship between the research variables. The results of the multiple regression calculations yielded the equation Y = 4.024 + 0.452 (X1) + 0.306 (X2), which means that if the constant value is 4.024, and the independent variables of work discipline (X1) and occupational health and safety (K3) (X2) are both 0, the employee performance (Y), as the dependent variable, will be 4.024 units. Based on the results of the research, it is shown that work discipline has a positive and significant effect on occupational health and safety (K3), work discipline has a positive and significant effect on employee performance, and occupational health and safety (K3) has a positive and significant effect on employee performance. Furthermore, work discipline has a positive and significant direct effect on performance through occupational health and safety (K3).